Correlation of microbiomes in “plant-insect-soil” ecosystem - Li, Guomeng; Liu, Peng; Zhao, Jihan; Su, Liangyinan; Zhao, Mengyu; Jiang, Zhengjie; Zhao, Yang; Yang, Xiping (Frontiers in Microbiology, 2023)
Traditional chemical control methods pose a damaging effect on farmland ecology, and their long-term use has led to the development of pest resistance. Here, we analyzed the correlations and differences in the microbiome present in the plant and soil of sugarcane cultivars exhibiting different insect resistance to investigate the role played by microbiome in crop insect resistance. We evaluated the microbiome of stems, top soil, rhizosphere soil, and striped borers obtained from infested stems, as well as soil chemical parameters of the soil. Results showed that microbiome diversity was higher in stems of insect-resistant plants, and in contrast, lower in the soil of resistant plants, with fungi being more pronounced than bacteria. The microbiome in plant stems was almost entirely derived from the soil. The microbiome of insect-susceptible plants and surrounding soil tended to change towards that of insect-resistant plants after insect damage. Insects’ microbiome was mainly derived from plant stems and partly from the soil. Available potassium showed an extremely significant correlation with soil microbiome in soil. This study validated the role played by the microbiome ecology of plant-soil-insect system in insect resistance and provided a pre-theoretical basis for crop resistance control.